Transformation of Future Educators: A Comprehensive Evaluation of Real Work Lectures (KKN) and Thematic School Field Introductions (PLP) at the Faculty of Teacher Training and Education - Kurniawan, Dydik; Bachri, Bachtiar Sjaiful; Mauren, Irena Yolanita (Universitas Trunojoyo Madura, 2023)
The purpose of this study was to examine the evaluation of the Thematic Integrated Community Service Programme (KKN) and School Field Introduction (PLP). Method used in this research is the countenance stake evaluation model, The research sample included 98 lecturers, 523 students, 47 principals, and 246 teachers from elementary, middle, and high schools and PKBMs in Samarinda. Data collection techniques are: Questionnaires, interviews, and document analysis. this study uses Descriptive Statistics. the research findings highlight the evaluation of the Thematic Community Service (KKN) and School Field Introduction (PLP) programmes from different perspectives, including school principals, FETT lecturers, students, and teachers. The findings align with previous research on effective programme planning, organization, assessment practices, experiential learning, student engagement, programme satisfaction, and teacher skills. The convergence of positive ratings across the evaluations indicates the potential effectiveness of the programmes in engaging students, improving learning outcomes, and meeting the needs of the school community. a conclusion can be drawn that: data from various perspectives Students, principals, teachers, and lecturers rated the implementation of the program as good or very good, highlighting its ability to provide valuable learning experiences for students. The program is seen as relevant to the curriculum and has a positive impact on increasing students' interest in pursuing a career in education. Additionally, the design and structure of the program were highly regarded, emphasizing its well-planned approach.